2021
DOI: 10.1186/s12915-021-00999-1
|View full text |Cite
|
Sign up to set email alerts
|

Sea urchin larvae utilize light for regulating the pyloric opening

Abstract: Background Light is essential for various biological activities. In particular, visual information through eyes or eyespots is very important for most of animals, and thus, the functions and developmental mechanisms of visual systems have been well studied to date. In addition, light-dependent non-visual systems expressing photoreceptor Opsins have been used to study the effects of light on diverse animal behaviors. However, it remains unclear how light-dependent systems were acquired and diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 54 publications
0
27
0
Order By: Relevance
“…Because it is reasonable to speculate that the cessation of forward swimming and/or the reversal of swimming direction after photoirradiation is mediated by a complex system including photoreceptors, neurons, and ciliary cells, we attempted to identify the most important body parts for this response by removing the larval anterior neuroectoderm (ANE) and/or postoral arms and then observing larval swimming behaviors. It has already been shown that this microdissection method is useful for investigating the essential parts of the body for a targeted phenomenon [ 12 ]. The cessation of forward swimming or reversal of swimming direction after photoirradiation was observed in 80% of the normal H .…”
Section: Resultsmentioning
confidence: 99%
“…Because it is reasonable to speculate that the cessation of forward swimming and/or the reversal of swimming direction after photoirradiation is mediated by a complex system including photoreceptors, neurons, and ciliary cells, we attempted to identify the most important body parts for this response by removing the larval anterior neuroectoderm (ANE) and/or postoral arms and then observing larval swimming behaviors. It has already been shown that this microdissection method is useful for investigating the essential parts of the body for a targeted phenomenon [ 12 ]. The cessation of forward swimming or reversal of swimming direction after photoirradiation was observed in 80% of the normal H .…”
Section: Resultsmentioning
confidence: 99%
“…The association of these photoreceptors with pigment cells suggests that sea urchin larvae might be capable of directional light perception [ 4 ]. Indeed, the activity of the digestive tract in sea urchin larvae is regulated in response to light, by a mechanism depending on opsin3.2, which indicates that the photoreceptors are capable of initiating a behavioral response upon stimulation with light [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the c-opsin opsin1 is expressed in several tissues of adult sea urchins and in other echinoderms [ 32 ]. In sea urchin larvae, the expression of the Go-opsin opsin3.2 was detected in cells that were described as non-directional photoreceptors [ 33 ], and opsin3.2 was shown to be involved in the behavioral response to light [ 34 ]. These studies suggest that functional photoreceptor cells are present in sea urchin larvae, although the cell type identity of these photoreceptors has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…A potential explanation may be due to decreased level of serotonin (Fig. 6A), as it has been shown that serotonin binds to the receptors near the pyloric sphincter to allow for sphincter opening 42 . Since we observe a trend in decreased gut contractions in the NeuroD1 TP injected larvae, whereas miR-124 inhibition and NeuroD1 overexpression resulted in significant decrease in gut contractions compared to the control, this suggests that miR-124 is likely to regulate NeuroD1 and an additional unknown factor to impact gut contractions (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…SoxB1, Six3, and Nkx2-3 expression in the endomesoderm could specify the foregut as neuroenderm but this had not been proven 40 . Recently, it has been shown that the opening of the pyloric sphincter is responsive to light, as a result of released serotonin that bind to the receptors in the midgut to mediate contraction 42 . During the larval stage, in response to calcium influx and release of different neurotransmitters, neurons in these three neuronal domains mediate swimming and feeding behavior which is vital for proper development.…”
Section: Introductionmentioning
confidence: 99%